ANALISIS DAMPAK LINGKUNGAN BUDIDAYA IKAN DALAM KERAMBA DI WADUK SUNGAI PAKU KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Yulhadis Yulhadis; Usman M. Tang; Nursyirwani Nursyirwani (Program Pascasarjana Universitas Riau, 2018)
The study was conducted in January-March 2018, field analysis (insitu) was conducted in Sungai Paku Reservoir of Sungai Paku Village Kampar Kiri Sub-district Kampar District Riau Province. Laboratory analysis (exsitu) was conducted in Ecology and Waters Management Faculty of Fishery and Marine Science University of Riau Pekanbaru. The purpose of this research is to analyze the quality of Sungai Paku reservoir to the floating net cage (FNC) activity, to analyze and develop the socialization of FNC management in the Sungai Paku reservoir. This research uses survey method, by conducting direct measurement in the field, conducting analysis and interviews of research location through questionnaire to get more accurate data. To analyze the environment at about 3 different stations over the inlet of the reservoir, within the FNC area, and outlet of the reservoir. Physical chemistry parameters include 95-95.2 cm Brightness, temperature 30-30.3oC, current velocity 3.92 - 3.97, dissolved oxygen 0.98 - 1.00 mg / l, pH 5, Phosphate 0.1850-0.1851 mg / L, nitrate 0.2102-0.2104 mg / l , ammonia 0.0675-0.0677 mg / l. The average abundance of phytoplankton 17,600 - 22,400 cells / ml. Abundance of macrozoobenthos 866 - 1471 Ind / m2. Evaluation of water quality at each observation station indicates that the recording at each station is DO, pH and total P which have not meet the standard of water quality.